An auxin controls bacterial antibiotics production. Issue 21 (24th August 2018) - Matilla, Miguel A; Daddaoua, Abdelali; Chini, Andrea; Morel, Bertrand; Krell, Tino
Abstract: The majority of clinically used antibiotics originate from bacteria. As the need for new antibiotics grows, large-scale genome sequencing and mining approaches are being used to identify novel antibiotics. However, this task is hampered by the fact that many antibiotic biosynthetic clusters are not expressed under laboratory conditions. One strategy to overcome this limitation is the identification of signals that activate the expression of silent biosynthetic pathways. Here, we report the use of high-throughput screening to identify signals that control the biosynthesis of the acetyl-CoA carboxylase inhibitor antibiotic andrimid in the broad-range antibiotic-producing rhizobacterium Serratia plymuthica A153. We reveal that the pathway-specific transcriptional activator AdmX recognizes the auxin indole-3-acetic acid (IAA). IAA binding causes conformational changes in AdmX that result in the inhibition of the expression of the andrimid cluster and the suppression of antibiotic production. We also show that IAA synthesis by pathogenic and beneficial plant-associated bacteria inhibits andrimid production in A153. Because IAA is a signalling molecule that is present across all domains of life, this study highlights the importance of intra- and inter-kingdom signalling in the regulation of antibiotic synthesis. Our discovery unravels, for the first time, an IAA-dependent molecular mechanism for the regulation of antibiotic synthesis.